SEM-based analysis of antennal sensilla of the parasitoid, Encarsia formosa Gahan (Hymenoptera: Aphelinidae). (3rd April 2019) - Liao, An-Qi; Song, Cheng-Cheng; Sun, Ze; Wang, Man-Qun
Abstract: Encarsia formosa is a parasitoid wasp, which has been extensively employed worldwide for controlling whitefly pests. There is a growing body of literature that recognises the importance of studying the morphological features and distributions of the antennal sensilla of parasitoids. The research data for this study were obtained by the JOEL JSM-6390LV scanning electron microscope. Results showed that the antenna of E. formosa is comprised of nine antennomeres, which includes six flagella, a pedicel, a scape and a radicle. This study identified and described eight types of sensilla: (1) Nonporous sensilla trichodea; and (2) Uniporous sensilla trichodea (ST-UP) which both are two subtypes of sensilla trichodea; (3) Multiporous sensilla placoid which could be clearly observed due to the largest size compared with other types of sensilla; (4) Chaetica sensilla which looks similar to ST-UP but could be distinguished by the apical pore; (5) Uniporous rod-like sensilla (RO-UP); and (6) Nonporous finger-like sensilla (FL-NP) which both are located in the exploration area of the distal flagellum; (7) The RO-UP sensilla which have a rod-like shape; and (8) The FL-NP which are inserted into bulbous stalks.